Pengaruh Harga Produk, Kualitas Produk, dan Brand Image Terhadap Keputusan Pembelian Aqua di Kota Kendal - Muhammad Alvinnur Budiansyah; Aqmala, Diana; Eko Waluyo, Dwi; Setiawan, Aries (LPPM Universitas Sains dan Teknologi Komputer, 2025)
Aqua, as a leading bottled mineral water brand in Indonesia, faces challenges in maintaining its market share amid increasing competition and boycott issues. This study aims to analyze the impact of product quality, product pricing, and brand image on purchasing decisions for Aqua in Kendal City. The research employs both quantitative and qualitative methods. Data collection techniques involve distributing questionnaires to 188 respondents and conducting interviews with 10 respondents. The respondents were selected using purposive sampling based on specific criteria, such as having used Aqua and being aware of the boycott issue. The data were analyzed using multiple linear regression to test the influence of each independent variable on the purchasing decision. The results show that product quality, product pricing, and brand image have a positive and significant impact on Aqua's purchasing decisions. Brand image emerged as the most dominant factor influencing purchasing decisions. Additionally, the majority of informants are highly concerned about the boycott issue and disturbed by the Israeli attacks, which has affected their purchasing decisions. This study recommends that Aqua improve product quality, implement competitive pricing strategies, and strengthen its brand image through innovation and marketing campaigns to maintain customer loyalty. Aqua should also promote its neutral stance publicly, clarifying that it is not involved in the Israel-Palestine issue, in order to maintain public trust in the brand.